SLANG WORDS USED BY LIVE CHAT OF VALKYRAE LIVESTREAM ON YOUTUBE - I Komang Aris Budi Ardianta; I Made Rajeg Rajeg; Anak Agung Sagung Shanti Sari Dewi (CV. Ulil Albab Corp, 2022)
Abstract: This study aimed to analyze the types of slang words used in the live chat of Valkyrae’s live stream on youtube. The data were taken from two of Valkyrae’s previous streams on YouTube. They were collected using observation and documentation methods. Then, they were analyzed using the theory of slang words by Allan and Burridge (2006). The results showed that all the types of slang words, namely Flippant, Fresh and Creative, Clipping, Imitative, and Acronym, were used by the chatters of Valkyrae’s viewers.